Morphometric study of the species Hypocoprus latridioides Motschulsky, 1839 and H. quadricollis Reitter, 1877 (Coleoptera: Atomariinae) - Otero, José (Entomologica Fennica, 2002)
Most of the characters used in the literature to distinguish H. latridioides Motschulsky, 1839 from the closely related taxon H. quadricollis Reitter, 1877 are not diagnostic. The present morphometric study indicates that there is no evidence to support the status of the latter as a separate species. A new description of H. latridioides is presented.